2022
DOI: 10.1021/acs.jmedchem.2c00548
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Class of Uracil Derivatives as Potential Mixed Lineage Kinase Domain-like Protein (MLKL) Inhibitors

Abstract: Necroptosis is a form of programmed cell death. Mixed lineage kinase domain-like protein (MLKL) is the necroptosis executor, and it is involved in various diseases such as tissue damage and neurodegeneration-related diseases. Here, we report the development of novel MLKL inhibitors with a uracil nucleus through scaffold morphing from our previously reported xanthine MLKL inhibitor TC13172. After a rational structure–activity relationship study, we obtained the highly potent compounds 56 and 66. Mechanism studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It was observed that these uracils did not inhibit necroptosis in MEF cells (stimulated with TNF, a SMAC mimetic, and zVAD.fmk), suggesting that they targeted the Cys86 in human MLKL that is not present in mouse MLKL. Furthermore, the binding of both uracil 38 and 39 to MLKL was shown to outcompete that of TC13172 35 in a pull-down assay . The binding of 38 to Cys86 was then confirmed by incubation with the MLKL protein and analysis via MS/MS, as well as mutagenesis studies wherein 38 and 39 failed to inhibit necroptosis in HT29 cells transfected to express a C86S mutant .…”
Section: Development Of Necroptosis Inhibitorsmentioning
confidence: 90%
See 4 more Smart Citations
“…It was observed that these uracils did not inhibit necroptosis in MEF cells (stimulated with TNF, a SMAC mimetic, and zVAD.fmk), suggesting that they targeted the Cys86 in human MLKL that is not present in mouse MLKL. Furthermore, the binding of both uracil 38 and 39 to MLKL was shown to outcompete that of TC13172 35 in a pull-down assay . The binding of 38 to Cys86 was then confirmed by incubation with the MLKL protein and analysis via MS/MS, as well as mutagenesis studies wherein 38 and 39 failed to inhibit necroptosis in HT29 cells transfected to express a C86S mutant .…”
Section: Development Of Necroptosis Inhibitorsmentioning
confidence: 90%
“…A scaffold-morphing strategy identified the hit compound 37 , with EC 50 = 3380 nM in HT29 cells treated with necroptotic stimulus (TNF, a SMAC mimetic, and zVAD.fmk). Elaboration of the SAR around this scaffold resulted in the development of uracils 38 and 39 (Figure ) with markedly improved potencies (EC 50 = 82 and 31 nM, respectively) . Importantly, these optimized uracils showed little-to-no inhibition of RIPK1 (18 and 0% at 10 μM, respectively) and no inhibition of RIPK3 in ADP-Glo enzymatic assays, as well as no effects on the level of MLKL phosphorylation.…”
Section: Development Of Necroptosis Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations